Self-assembly of synthesized 4-pentynoic acid functionalized magnetite-maghemite nanoparticles on silicon dioxide/n-type silicon substrate / Aainaa Aqilah Baharuddin - Aainaa Aqilah, Baharuddin (2017)
This study is divided into two parts; i) synthesis of the functionalized magnetite-maghemite (Fe3O4-γ-Fe2O3) nanoparticles (FNPs) and ii) self-assembly of the FNPs on silicon substrate which serves as metal-oxide-semiconductor capacitor. Bare iron oxide nanoparticles (NPs) were synthesized by co-precipitation method and were altered to pH 12 (optimum pH) using NH4OH to promote dispersity right before ex-situ modification with oleic acid (0.2-0.8 g/g oleic acid to iron oxide) and subsequent 4-pentynoic acid (1.63 mmol) functionalization. In the first part, X-ray-diffraction (XRD) showed that lattice constants of the iron oxides co-exist as Fe3O4-γ-Fe2O3. Transmission electron microscopy showed that the particle size (10.94 ± 0.24 nm) of sample P-0.4 is complementary to the mean crystallite size (10 ± 1 nm) attained from XRD. Thermogravimetric-differential thermal analysis indicated that monolayer oleic acid FNPs was produced for ex-situ modification of 0.2 g/g oleic acid to iron oxide. Whereas higher concentrations of oleic acid ex-situ modifications generated bilayer oleic acid-coated FNPs to which, functionalization of 4-pentynoic acid was only successfully performed as indicated by Fourier transform infrared spectroscopy. Zetasizer affirmed the highly stabilized dispersion of FNPs at pH 12 with zeta potentials at relatively -47 to -75 mV and mean hydrodynamic particle size distributions of ~35-48 nm. Sample 0.4 g/g oleic acid to iron oxide, functionalized with 4-pentynoic acid, with the most stabilized nanoparticles in an aqueous medium was chosen for self-assembly in the second part. In the second part, investigation on the relation between temperature-influential self-assembly (70-300 ˚C) of the samples on SiO2/n-Si structure with their electrical characteristics was conducted. XRD analysis revealed that 8 ± 1 nm of FNPs which aggregated non-uniformly into film of 12.6 μm thickness was self-assembled via Si-O-C linkages. Besides, increasing temperature of heat treatments induced growth of native oxide, SiO2 on the Si substrate. Other implications of increasing heating iii temperature disclosed by attenuated total reflectance infrared analysis are breakdowns of Si-O-C linkages and formations of Si-OH defects. Atomic force microscopy implied that sample with more physisorbed surfactants exhibited the highest root-mean-square roughness (18.12 ± 7.13 nm) and vice versa (12.99 ± 4.39 nm). The increased saturation magnetization (71.527 A·m2/kg) and coercivity (929.942 A/m) acquired by vibrating sample magnetometer of the sample heated at 300 ˚C verified the surfactants’ disintegration. Leakage current density-electric field characteristics signified that sample heated at 150 ˚C with the most aggregated FNPs as well as the most developed Si-O-C linkages demonstrated the highest breakdown field and barrier height at 2.58 x 10-3 MV/cm and 0.38 eV respectively. Whereas sample heated at 300 ˚C with the least Si-O-C linkages and more Si-OH defects as well as lesser aggregated NPs showed the lowest breakdown field and barrier height at 1.08 x 10-3 MV/cm and 0.19 eV respectively.